Dinámica poblacional bacteriana del Lago de Cuitzeo, Michoacán, México - Pedraza Agustín, Iris (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
The total bacterial population dynamics, total coliforms, Escherichia coli and Pseudomonas, Vibrio and Salmonella genre were studied. Four sampling campaigns were performed between November 2006 and March 2007, taking samples from eight sites into the lake. Some water physicochemical parameters were analyzed in order to determine their influence on the bacterial population. The bacterial total density changed during the studied period, standing out the sites Cuitzeo in December and Río Grande in November. It was not found a behavior pattern since it was varying at almost each site. The total coliform population was stable at all sites. A variation of faecal coliform density was found along the study but Río Grande was always the site with the highest values. Otherwise, Pseudomonas population showed almost the highest concentrations in February. Vibrio genre had the highest density in March. Salmonella population had the greatest values in November in almost all sites but it was not found in some other sites. The presence of Pseudomonas was more representative than Vibrio and Salmonella. It was also observed an inverse relationship between Pseudomonas density and E. coli, finding less E. coli presence at the sites where Pseudomonas showed high density. An association between some environmental characteristics and the bacterial density was detected; for example, the sites where the highest bacterial total population and E.coli were detected are the sites with the lowest electrical conductivity, salinity, dissolved oxygen values and the lowest Pseudomonas and Vibrio concentrations. Moreover, it was observed an influence in some parameters depending on the sampling campaign.

En este trabajo se analizó la dinámica poblacional bacteriana total, coliformes totales, Escherichia coli y los géneros Pseudomonas, Vibrio y Salmonella. Se realizaron cuatro muestreos de agua en ocho sitios distribuidos en el lago de Cuitzeo, determinando algunos parámetros fisicoquímicos para analizar la influencia de éstos sobre las poblaciones bacterianas mencionadas. El período de muestreos comprendió los meses de noviembre y diciembre de 2006, y febrero y marzo de 2007. La densidad total bacteriana varió durante los muestreos, destacando por su alta densidad los sitios de Cuitzeo en diciembre y Río Grande en noviembre. No se encontró un patrón de comportamiento pues fue fluctuante en casi todos los sitios. Además, se observó que la población de coliformes totales se mantuvo constante en todos los sitios. Respecto a coliformes fecales se encontró una variación en la población, pero el sitio que siempre presentó los valores más altos fue Río Grande. Por otra parte, la población del género Pseudomonas, fue más alta en 6 de los 8 sitios de muestreo durante el mes de febrero. El género Vibrio mostró la mayor densidad en el mes de marzo. La población de Salmonella fue más alta durante noviembre en la mayoría de los sitios y en algunos no se detectó. La presencia de Pseudomonas fue más abundante que los géneros Vibrio y Salmonella. Se observó también, una relación inversa entre las poblaciones bacterianas de Pseudomonas y E. coli, encontrando que en donde hay más organismos del género Pseudomonas hay una concentración menor de E. coli.
Facultad de Biología. Maestría en Conservación y Manejo de Recursos Naturales
Keywords: info:eu-repo/classification/cti/2; FB-M-2007-0101; Bacteria; Lago; Contaminación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6545